Radiomics to Assist in Decision Making and Improve Precision Medicine - Nichols, Emma Hitt (MD Conference Express, 2015)
Radiomics is opening new possibilities for data collection and improved decision making in treating cancer. This article addresses the advances in the use of radiomics and radiogenomics and how this will affect the future practice of radiologists.